What matters in patient-centered medical home transformation: Whole system evaluation outcomes of the Brown Primary Care Transformation Initiative. (14th June 2018) - Goldman, Roberta E; Brown, Joanna; Stebbins, Patricia; Parker, Donna R; Adewale, Victoria; Shield, Renee; Roberts, Mary B; Eaton, Charles B; Borkan, Jeffrey M
Objectives: Patient-centered medical home transformation initiatives for enhancing team-based, patient-centered primary care are widespread in the United States. However, there remain large gaps in our understanding of these efforts. This article reports findings from a contextual, whole system evaluation study of a transformation intervention at eight primary care teaching practice sites in Rhode Island. It provides a picture of system changes from the perspective of providers, staff, and patients in these practices. Methods: Quantitative/qualitative evaluation methods include patient, provider, and staff surveys and qualitative interviews; practice observations; and focus groups with the intervention facilitation team. Results: Patient satisfaction in the practices was high. Patients could describe observable elements of patient-centered medical home functioning, but they lacked explicit awareness of the patient-centered medical home model, and their activation decreased over time. Providers' and staff's emotional exhaustion and depersonalization increased slightly over the course of the intervention from baseline to follow-up, and personal accomplishment decreased slightly. Providers and staff expressed appreciation for the patient-centered medical home as an ideal model, variously implemented some important patient-centered medical home components, increased their understanding of patient-centered medical home as more than specific isolated parts, and recognized their evolving work roles in the medical home. However, frustration with implementation barriers and the added work burden they associated with patient-centered medical home persisted. Conclusion: Patient-centered medical home transformation is disruptive to practices, requiring enduring commitment of leadership and personnel at every level, yet the model continues to hold out promise for improved delivery of patient-centered primary care.